Selective Suppression: Relations between Civil Society Organizations and the State in Zimbabwe - Mpani, Nyasha Mcbride (Department of Sociology, 2022)
This study assessed whether civil society organizations in Zimbabwe that have previously been suppressed by the state, currently experience any change in their relations with the state under the Mnangagwa Presidency. I adopted a case study approach to comparatively assess the experiences of two civil society organizations relations with the state over a two- year period. The two case studies are of the Zimbabwe Congress of Trade Unions (ZCTU) and the Amalgamated Rural Teachers Union of Zimbabwe (ARTUZ). Selected media sources, including the organizations' social media (i.e., Facebook, websites, and Twitter) and non-state news media, were used to obtain mainly qualitative data and basic numerical information. Gramsci's theory of hegemony and Foucault's concept of ‘panoptic surveillance' informed my analytical framework. The findings show that state suppression is at the core of the relations between state and civil society organizations that are critical of the state in Zimbabwe. The recurring forms of suppression include arrests, detention, assaults, abduction, torture, raids, theft, surveillance, judicial harassment, cyber-attacks/smear campaigns, travel bans, salary cessation and abuse. The findings suggest that ongoing state suppression is worse than during the latter part of Mugabe's Presidency. Selective suppression of targeted civil society organizations that are critical of the state also reflects diminishing democracy in Zimbabwe. This appears to be a general pattern in the region and one possible reason why bodies such as African Union and the Southern African Development Community are reluctant to discipline member states, including Zimbabwe, for human rights violations or state repression of critics.